Between here and forever - Scott, Elizabeth, 1972- (Simon Pulse, 2011)
When her older, "perfect" sister Tess has a car accident that puts her in a coma, seventeen-year-old Abby, who has always felt unseen in Tess's shadow, plans to bring her back with the help of Eli, a gorgeous boy she has met at the hospital, but her plans go awry when she learns some secrets about both Tess and Eli, enabling her to make some decisions about her own life.